EXPLORING THE DEVELOPMENT OF NEUROSCIENCE IN THE LIGHT OF ISLAMIC PERSPECTIVES: A QUALITATIVE LITERATURE REVIEW - Mohammad Jailani (IAIN Ambon, 2023)
The study aims to investigate the correlation between neuroscience and Islamic principles, addressing the notion that neuroscience is not considered an Islamic discipline due to its emergence after the revelation of the Qur'an and Sunnah in the 7th century. Utilizing a literature review approach, the researcher collected data from scientific online publications and academic sources available on Google Scholar, incorporating both scientific and religious perspectives. The research employs the theory of Prof. Amen Abdullah, which combines the values of science and religion to analyze the data through content analysis techniques. The findings of this research reveal the significant role of the fontanel (Frontal Lobe) located within the human brain, serving as a crucial center for transmitting nerve cell impulses to other sensory organs. This communication is facilitated through neurotransmitters, acting as a crucial communication center between nerve cells. Consequently, the frontal lobe plays a pivotal role in human intelligence and personality, empowering individuals to utilize their minds in enhancing the quality of their thinking. The implications of this research underscore the potential of human beings as intelligent entities, aligning science and religion in the development of Islamic studies and education. Researchers are encouraged to enrich their findings by collaborating with neuroscience experts to ensure a comprehensive interpretation of the Qur'an that resonates with contemporary scientific discoveries.